Neuroprotection Against Parkinson’s Disease Through the Activation of Akt/GSK3β Signaling Pathway by Tovophyllin A - Huang, Yanjun; Sun, Lirong; Zhu, Shuzhen; Xu, Liu; Liu, Shuhu; Yuan, Chunhua; Guo, Yanwu; Wang, Xuemin (Frontiers in Neuroscience, 2020)
Parkinson’s disease (PD) is one of the most prevalent and life-threatening neurodegenerative disease and mainly characterized by lack of sufficient dopaminergic neurons in the substantia nigra pars compacta (SNc). Although current treatments help to alleviate clinical symptoms, effective therapies preventing neuronal loss remain scarce. Tovophyllin A (TA), one of the xanthones extracted from Garcinia mangostana L. (GM), has recently been reported to play a beneficial role in the therapy of neurodegenerative diseases. In our research, we explored whether TA has protective effects on dopaminergic neurons in PD models. We found that TA significantly reduced apoptotic cell death in primary cortical neurons treated with 1-methyl-4-phenyl pyridinium (MPP+) or Paraquat (PQ) in the in vitro PD model. In an in vivo acute PD model induced by 1-methyl4-phenyl-1,2,3,5-tetrahydropyridine (MPTP) treatment, TA also attenuated the resulting behavioral dysfunctions and dopaminergic neuron loss. In the collected brain tissues, TA increased the phosphorylation of Akt and GSK-3β, which may be related to TA-mediated dopaminergic neuronal protective effects. In summary, our results illustrated that TA is a powerful cytoprotective agent for dopaminergic neurons in the MPTP-induced PD model, suggesting TA as a possible therapeutic candidate for PD.